THE ROLE AND IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH (Eureka Journal of Education & Learning Technologies, 2026)
This scientific article explores the role and significance of Artificial Intelligence (AI) in English language teaching and its contribution to improving the quality of education in the modern learning environment. The study highlights how AI technologies support personalized learning, enhance students’ language competencies, simplify assessment procedures, and increase the effectiveness of teaching practices. In addition, the article discusses the opportunities and challenges associated with the implementation of AI in English language education.The findings reveal that the appropriate integration of AI-based tools can significantly improve students’ motivation, autonomous learning skills, and overall language proficiency.
Keywords: Artificial intelligence, English language teaching, educational technologies, digital education, personalized learning, innovation, language skills, interactive learning.